Chemokine ligand 14 correlates with immune cell infiltration in the gastric cancer microenvironment in predicting unfavorable prognosis - Lu, Bing; Shi, Jiawen; Cheng, Tong; Wang, Congshuo; Xu, Manyu; Sun, Pingping; Zhang, Xiaojing; Yang, Lei; Li, Peng; Wu, Han; Kuai, Xiaoling (Frontiers in Pharmacology, 2024)
Objective: Gastric cancer (GC) is the world's second-leading cause of cancer-related mortality, the prognosis for GC patients remains poor in terms of a lack of reliable biomarkers for early diagnose and immune therapy response prediction. Here, we aim to discover the connection between CCL14 expression in the gastric tumor microenvironment (TME) and its clinical significance and to investigate its correlation with immune cell infiltration.We assessed CCL14 mRNA expression and the interrelation with tumorinfiltrating immune cells (TILs) using bioinformatics analysis in gastric cancer. CCL14 protein expression, TILs, and immune checkpoints were detected by multiple immunohistochemistry in gastric cancer tissue microarrays. Then we conducted statistical analysis to determine the associates between CCL14 related patient survival and the relationship between the expression of CCL14 and infiltrated immune cell markers (P < 0.05).We found that the CCL14 protein was separately expressed in carcinoma cells and TILs in stomach cancer tissues. CCL14 protein was related to tumor differentiation, tumor depth, and positively correlated with the presentation of LAG3 and PD-L1 presentation in gastric cancer cells. In addition, the CCL14 protein in TILs of gastric cancer tissues was related to Lauren's type, T cells (CD4 + , CD8 + ), and CD68 + Macrophages in TME. Kaplan-Meier survival and Multivariate analyses showed that the CCL14 expression in gastric cancer cells was an independent prognostic factor.Conclusion: Our study illustrated that CCL14 is a poor prognosis biomarker in gastric cancer, which showed a trend of CCL14-related immunotherapy benefits in patients.CCL14; tumor microenvironment; tumor-infiltrating immune cells; immune checkpoint; chemokine drug target